Leadership as a Catalyst: Promoting Teacher Mental Health and Well-being in Islamic Education - Lukman (Journal of Educational Management Research, 2025)
This study aims to investigate the transformational leadership role of Madrasah Heads in supporting teachers' mental health in MAN I Plus Skills Bengkalis. This issue is relevant considering psychological challenges such as stress and burnout are often faced by educators. Using a qualitative approach and a single-case study design, this study examines the leadership practices that directly impact teachers' mental well-being from the perspective of their personal experiences. In-depth interviews with madrasah heads and teachers, as well as document analysis, reveal that effective leadership is characterised by three main strategies: serving as a mentor and emotional supporter; fostering a participatory and collaborative work environment; and establishing policies that promote work-life balance. These findings confirm that leadership interventions focused on the humanitarian and psychological aspects have a significant impact on increasing teacher motivation, resilience, and job satisfaction. Implicitly, this study recommends that education leaders adopt a holistic approach that prioritizes the psychological well-being of teachers, ultimately improving the quality of teaching and the sustainability of educator professionalism.